Analysis Of The Effect Of Organizational Culture On Performance Of Employees (Case Study Of The Kominfo Office Of Pariaman City) - Mulia, Rizki Afri; Putri, Rianda Prima; Saputra, Nika (Jurnal Ilmiah Ekotrans & Erudisi, 2021)
This study aims to analyze, Influence Organizational Culture Against Employee Performance At the Office of Communications and Information Technology of Pariaman. This research is a quantitative research that shows a causal relationship. The sample in this study were 47 employees. Data collection techniques used were observation, questionnaire and documentation. Data analysis techniques used are descriptive statistical analysis using percentages, averages, and standard deviations and for inferential statistical analysis using data normality tests, simple linear regression analysis, and product moment correlation analysis. The results of the study show that the organizational culture is in a very good category in terms of indicators, namely: Innovation and Courage to take risks; Attention to detail; Results oriented; Human oriented; Team oriented; Aggressive; and stable. Employee performance is in a very good category in terms of indicators of discipline of service personnel, responsibility of service personnel, ability of service personnel, politeness and friendliness of officers, based on simple linear regression analysis shows that there is an influence of organizational culture on employee performance at the Pariaman City Communication and Information Agency Pariaman City. From the results of product moment correlation analysis obtained a significant level of relationship between the influence of organizational culture on the performance of employees at the Office of Communication and Information Office of , Pariaman City with the Strong category.